Identificação por microscopia Raman de pigmentos da pintura a óleo "Retrato de Murilo Mendes" de Cândido Portinari - Oliveira,Luiz Fernando Cappa de (1998)
In the present work "ex situ"Raman microscopy was employed in the identification of some of the pigments present in the painting "Portrait of Murilo Mendes" by Cândido Portinari. In the investigated samples it was possible to identify unambiguously two pigments: Prussian blue and lapis-lazuli (or its synthetic analogue, ultramarine blue) - the former is observed together with organic substances, possibly used as dispersants, what suggests a further use of a mass for recover the painting.